2017
DOI: 10.1093/neuonc/nox026
|View full text |Cite
|
Sign up to set email alerts
|

Mutational burden, immune checkpoint expression, and mismatch repair in glioma: implications for immune checkpoint immunotherapy

Abstract: To clarify the relationships among TML, MMR, and immune checkpoint expression, we profiled the frequency of shared biomarker phenotypes. On the basis of a variety of potential biomarkers of response to immune checkpoints, only small subsets of glioma patients are likely to benefit from monotherapy immune checkpoint inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
294
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(315 citation statements)
references
References 44 publications
11
294
1
1
Order By: Relevance
“…Further studies will be needed to determine whether therapeutic drug combinations to manipulate these factors will, in turn, directly impact intratumoral immune cytolytic activity and lead to an immune-mediated anti-tumor effect. Consistent with other studies [7,27,35], we found no association between the non-synonymous TMB and the degree of intratumoral immune cytolytic activity in GBM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further studies will be needed to determine whether therapeutic drug combinations to manipulate these factors will, in turn, directly impact intratumoral immune cytolytic activity and lead to an immune-mediated anti-tumor effect. Consistent with other studies [7,27,35], we found no association between the non-synonymous TMB and the degree of intratumoral immune cytolytic activity in GBM.…”
Section: Discussionsupporting
confidence: 92%
“…However, despite promise in preclinical and early phase studies [2,3], single agent programmed death 1 (PD-1) inhibition is ineffective for recurrent GBM in the absence of a rare, markedly hypermutated tumor [46]. This is due, in part, to the relative paucity of intratumoral T cells in GBM compared to cancers with carcinogen-induced mutational signatures and high tumor mutational burden (TMB) [711]. Even in GBMs with higher than average TMB, there does not appear to be a resultant influx of CD8+ T cells or increase in PD-1/PD-L1 expression [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balachandran et al 2017; Brown et al 2014; Gros et al 2016; Hodges et al 2017; Lauss et al 2017; Linnemann et al 2015; Luksza et al 2017; Matsushita et al 2012; McGranahan et al 2016; Ock et al 2017; Pritchard et al 2015a; Rizvi et al 2015; Robbins et al 2013; Snyder et al 2014; Tran et al 2016; Van Allen et al 2015; van Rooij et al 2013; Verdegaal et al 2016). While these various tools have an important role to play in the prediction of immunogenic antigens, the majority of the identified epitopes do not initiate an immune response (e.g.…”
Section: Identification Of Neoantigensmentioning
confidence: 99%
“…Mildenberger et al (pp. 650-658) point out the limitations of checkpoint inhibitions in GBM in which several factors, including relatively low mutational load and neoepitopes, constitute negative predictive factor of response [11]. The situation could be different in recurrent low-grade gliomas, because the relatively slow growth of the tumor allows the accumulation of mutations, particularly in some patients pretreated with Temozolomide (hypermutator phenotype) and could also give enough time for an endogenous T-cell response to become effective.…”
Section: Improving Diagnosis and Management Of Primary Brain Tumorsmentioning
confidence: 99%